Proposed optomechanical systems based on luminescence-induced optical forces - Hideki Arahari; Sota Konishi; Kodai Takaoka; Seiji Akita; Hajime Ishihara (Physical Review Research)
We propose an optomechanical system utilizing luminescence-induced optical forces (LIOFs). Anisotropic dielectric structures enhance the recoil force from the luminescence. The optomechanical resonator consists of a composite film with a dielectric membrane, luminescent nanofilm, and a metallic substrate. The LIOF causes a mechanical frequency shift in the oscillator known as the optical spring effect. These results link the quantum properties of luminescent nanomaterials with those of other quantum-mechanical systems with vastly different frequency regimes via induced vibrational modes.